STRATEGI AKOMODASI KEPENTINGAN MASYARAKAT DALAM PENGELOLAAN TAMAN NASIONAL BANTIMURUNG BULUSARAUNG DI PROVINSI SULAWESI SELATAN - Abd. Kadir Wakka; San Afri Awang (Jurnal Analisis Kebijakan Kehutanan, 2015)
Functional convertion of partly forest area in the Maros Regency since 2004 to become the Bantimurung Bulusaraung National Park (Babul National Park) brings consequences for local community activities that have been going on for generations. The existence of community with their activities to meet their needs in the Babul National Park needs attention and should be considered and accommodated by Babul National Park manager by also considering the ecological condition. This study aims to formulate a strategy for accommodating community interests that suits to the Babul National Park conditions. Data collected through interviews and questionnaires to a number of expert informants and literature study. Data analyzed using analytical hierarchy process (AHP). Research results showed that the main factor to be considered in accommodating interests of the community is the level of dependency of community on Babul National Park. Based on the main factor, accommodation strategy of the community interests appropriate to the condition of Babul National Park is to conduct collaborative management. Babul National Park office as a driving force in implementating the strategy should establish communication and coordination with various related stakeholders as one of the requirements of the strategy implementation.